Lipid droplets in plants and algae: Distribution, formation, turnover and function. (December 2020) - Ischebeck, Till; Krawczyk, Hannah E.; Mullen, Robert T.; Dyer, John M.; Chapman, Kent D.
Abstract: Plant oils represent an energy-rich and carbon-dense group of hydrophobic compounds. These oils are not only of economic interest, but also play important, fundamental roles in plant and algal growth and development. The subcellular storage compartments of plant lipids, referred to as lipid droplets (LDs), have long been considered relatively inert oil vessels. However, research in the last decade has revealed that LDs play far more dynamic roles in plant biology than previously appreciated, including transient neutral lipid storage, membrane remodeling, lipid signaling, and stress responses. Here we discuss recent developments in the understanding of LD formation, turnover and function in land plants and algae.